Space weather predictions for LISA during solar cycle 26 - Grimani, C; Fabi, M; Sabbatini, F; Villani, M (Classical and quantum gravity, 2025)
The impact of space weather on space mission performance is a subject of extensive study by both scientists and space agencies. In this work, we discuss solar activity, the characterization of the interplanetary medium and the fluxes of solar and galactic particles after 2035, when laser interferometer space antenna (LISA), the first interferometer for low-frequency gravitational wave detection in space, is expected to be launched. According to the lessons learned with LISA Pathfinder, the precursor mission of LISA, we focus on interplanetary phenomena that have been demonstrated to affect mission performance. The results of the study presented here can be considered in any investigation concerning the internal charging of the LISA spacecraft.